The Relationship Between Knowledge and Readiness of PMR Members in Providing First Aid to Traffic Accident Victims at MAN 2 Banjarmasin - Claudia, Jesika; Santoso, Bagus Rahmat; Gaghauna, Eirene Eunike Meidiana (Universitas Ibn Khaldun Bogor, 2025)
The high mortality rate in traffic accident victims can be caused by improper provision of first aid. All levels of society must know how to perform first aid (First Aid). One of them is Senior High School (SMA) students who are members of the PMR extracurricular. Knowing the relationship between knowledge and readiness of PMR members in providing first aid to victims of traffic accidents in MAN 2 Banjarmasin. This study used quantitative methods with a Cross Sectional approach, with sample of 57 people. Data collection using questionnaire sheets and data analysis using Chi Square test. Most respondents had good knowledge as many as 38 people (38.0%) and most were ready to provide first aid to traffic accident victims as many as 42 people (42.0%). The results of the Chi-Square statistical test obtained a value of p = 0.000 < 0.05. It is concluded that PMR members who have good knowledge can influence readiness in providing first aid to victims of traffic accidents.